EFISIENSI PRODUKSI DAN PEMASARAN SERTA DAYA SAING KOMODITI KELAPA DALAM DI KABUPATEN NUNUKAN KALIMANTAN TIMUR - , ELLY JUMIATI, Prof. Dr. Ir. Dwidjono HD, MS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to know the production and marketing efficiency of coconut, and measure the comparative and competitive advantage of coconut. The Research was conducted in Nunukan Regency in the district of the eastern and northern part of Sebatik. Random sampling method was applied in this study. The stochastic frontier production function with Frontier program 4.1.c was applied to analyze production efficiency. Marketing efficiency was measured by marketing margins, market integration, correlation and price transmission, meanwhile the Policy Analysis Matrix (PAM) was applied to analyze the competitiveness. The results showed that farm production of coconut was efficient, as shown by the Economic Efficiency (EE) value of the average farmer of 0.771 or 77.1%, the value of technical efficiency (ET) average of 0.974 or 97.4%, and the value of allocative efficiency / price (EA) for the average farmer 0.798 or 79.8%. Factors that affect economic efficiency were formal education and other sources of income. There are two marketing channels in a coconut at the study site, which is the channel I: farmer - traders village / district â traders regency / cities â end consumer, and marketing channels to II: farmer - traders village / district - traders regency / cities - traders retailers â end consumers. Coconut commodity marketing in Nunukan regency was not efficient yet. This can be seen from the marketing margin on all marketing channels, unequal distribution margin, price share received by farmers is low, and ratio of benefits and costs vary. Based on the analysis of price transmission, price correlation, and market price transmission elasticity indicated that coconut marketing is imperfectly integrated market, while prices were not transmitted properly, market structure tends to be monopsony / oligopsony. The coconut commodity has competitive advantage but does not have a comparative advantage, as shown by the PCR values of 0.95 and 1.24 for DRC. However, financial analysis shows that private profit (PP) obtained for Rp 1,511,814.961 (advantageous), while the social benefits (SP) of Rp -2,665,869.951 indicated that coconut is not profitable, economically.